Effect of urbanization and its environmental stressors on the intraspecific variation of flight functional traits in two bumblebee species - Nicola Tommasi; Emiliano Pioltelli; Paolo Biella; Massimo Labra; Maurizio Casiraghi; Andrea Galimberti (Oecologia, 2022)
The way urbanization shapes the intraspecific variation of pollinator functional traits is little understood. However, this topic is relevant for investigating ecosystem services and pollinator health. Here, we studied how urbanization affects the functional traits of workers in two bumblebee species ( Bombus terrestris and B. pascuorum ) sampled in 37 sites along a gradient of urbanization in North Italy (an area of 1800 km 2 including the metropolitan context of Milan and other surrounding capital districts). Namely, we investigated the effect of land use composition, configuration, air temperature, flower resource abundance, and air pollutants on the variation of traits related to flight performance and of stress during insect development (i.e., wing size, wing shape and size fluctuating asymmetry). The functional traits of the two bumblebees responded idiosyncratically to urbanization. Urban temperatures were associated with smaller wing sizes in B. pascuorum and with more accentuated fluctuating asymmetry of wing size in B. terrestris . Moreover, flower abundance correlated with bigger wings in B. terrestris and with less asymmetric wing size in B. pascuorum . Other traits did not vary significantly, and other urban variables played minor effects. These species-specific variation patterns highlight that environmental stressor linked to urbanization negatively impact the traits related to flight performance and development stability of these syntopic bumblebees, with possible consequences on the pollination service they provide.